"On Cloud Nine": Positive memories in American Presidential Speeches (1945–2017). (February 2019) - Adams, Tracy; Vinitzky-Seroussi, Vered
In light of a long chain of horrific tragedies and catastrophes made by both nature and man, the current focus of memory studies on difficult pasts and shameful moments, and the expectation of political leaders to provide comfort and inspiration to their public, this article asks, 'Is commemoration with joy possible?' Based on an analysis of 860 American presidential public speeches, this article unpacks the category of positive memories by differentiating between memories of pride, joy, and benignity. It then analyzes the various sources, appearances, and frequency of such memories in ceremonial rhetoric. The article concludes by showing that while positive memories are still a minority they are significantly on the rise. Moreover, while party affiliation matters and effects the choices made by American Presidents, they all pay a unified homage to their predecessors, hinting at future legacy considerations that are untainted by politics.